Transação tributária no Brasil: supremacia do interesse público e a satisfação do crédito tributário - Parisi, Fernanda Drummond (2016)
This study is focused on the tax transaction between the Government and tax payers. The scope of the analysis of this legal institute, created to be an alternative way to set up tax obligations, goes beyond the interpretation of the instrument itself, covering theoretical and axiological assumptions contained explicitly or not, in the legal system. Tax transaction may be a mean of tax credits payment arising from law obligation, but as it is an alternative by regular payments, it does really need to be understood from a systemic point of view, covering the whole legal system. The transaction is not really new, but it hasn´t already been totally accepted by legal operators because there are a lot of prejudices regarding the alternative tax mean of payment. Actually people are still afraid that transaction become a legal tool to avoid taxation and may reduce state revenues compromising the supremacy of the public interest. The tax credits are required by Government activity endorsed by law contains and are protected by lots of rules that guarantees the liability presumed of credits obligations. That is why this study´s scenario seems to be so challenging. It seems very important to spend some reflection on this issue and to understand the tax payments in a bigger perspective, although it can´t be a complete study, it may bring some lights to the subject. The relevance of the study gets bigger considering the actual Judiciary crises, because it is outstanding knowledge of mostly law suits are filed by Public revenues in order to charge not payed taxes. So this study claims are indeed necessary and will be leaded by the new thinking about the supremacy of public interest and its impact on demand of tax debt